2005
DOI: 10.1097/01.tp.0000157278.02848.c7
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Effects of Extracorporeal Photopheresis Unraveled: Induction of Tolerogenic Dendritic Cells In Vitro and Regulatory T Cells In Vivo

Abstract: Extracorporeal photopheresis (ECP) may represent an alternative to immunosuppression, as a means of reducing rejection after thoracic organ transplantation. The mechanism by which ECP exerts its protective effects has, until now, remained elusive. We analyzed peripheral blood mononuclear cells of four children with chronic heart and lung transplant rejection, who received ECP in addition to conventional immunosuppressive treatment. The effects of ECP were evaluated at each cycle, comparing blood samples from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 20 publications
4
147
2
5
Order By: Relevance
“…5,6,14,17,[34][35][36][37] Our studies demonstrate that ECP treatment rapidly augments PMN-MDSCs, which dampen Th1 and Th17 T-cell responses. Therefore, these studies suggest that, in addition to inducing lymphocyte apoptosis and modulating adaptive immunity, ECP acts on the innate arm of the immune system by rapidly inducing a neutrophilic immunomodulatory MDSC population.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…5,6,14,17,[34][35][36][37] Our studies demonstrate that ECP treatment rapidly augments PMN-MDSCs, which dampen Th1 and Th17 T-cell responses. Therefore, these studies suggest that, in addition to inducing lymphocyte apoptosis and modulating adaptive immunity, ECP acts on the innate arm of the immune system by rapidly inducing a neutrophilic immunomodulatory MDSC population.…”
Section: Discussionmentioning
confidence: 94%
“…3,4 Despite its clinical effectiveness, the immunomodulatory mechanisms of ECP are not fully understood. 5 Previous studies proposed triggering of lymphocyte, monocyte and natural killer cell apoptosis, 6 the induction of regulatory T cells (Tregs), [7][8][9] including enhancement of Treg function, 10 modulation of pro-inflammatory cytokines and/ or induction of tolerogenic dendritic cells [11][12][13][14] as potential modes of ECP action. Immature B-cell subsets and levels of B-cell activating factor have been shown to serve as clinical ECPresponse markers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported that the frequency of T-cells with a regulatory phenotype and suppressive activity is increased during ECP treatment in GVHD patients [12,24] despite the fact that the circulating count does not reach the level observed in healthy donors [25]. This suggests that the induction of Treg cells could add its contribution to the generation of tolerogenic DCs.…”
Section: Mechanisms Of Action For Ecp: From T Lymphocytes Apoptosis Tmentioning
confidence: 95%
“…The lymphocytes die in 24-48 hour or even less time if activated, whereas monocytes are slow to progress toward apoptosis [10][11][12] and for few days, maintain the properties of differentiation and communication [13]. It appears in GVHD treated by ECP that the clinical benefits result from the processing of these apoptotic cells.…”
Section: Mechanisms Of Action For Ecp: From T Lymphocytes Apoptosis Tmentioning
confidence: 99%
“…• Clearance of apoptotic cells by antigen-presenting cells results in differentiation of those cells into a more tolerogenic phenotype 6,7 , leading to decreased stimulation of effector T cells or their deletion.…”
Section: Extracorporeal Photopheresismentioning
confidence: 99%